Cheese True Density Prediction by Linear Equations. Issue 4 (14th December 2012) - Iezzi, Romina; Locci, Francesco; Mucchetti, Germano
Abstract Knowledge of cheese density is necessary to accurately predict heat exchange rate occurring during cheese curd cooling or cheese processing, freezing and thawing. Cheese density data are poor in literature. True density of 22 different cheeses was measured by the water displacement method. Linear equations able to predict cheese density from its components mass fraction have been elaborated and validated. The best fit between measured and predicted values was obtained when all the major cheese components were considered in the equation. Also, equations based only on nonfat total solids or moisture and fat content gave a good prevision, resulting in an alternative to the universal formula based on components volume fraction that overestimates cheese true density, if air content is not taken into account. The proposed equations may become a powerful instrument to correctly predict true density and to improve accuracy of heat exchange prediction models. Practical Applications Equations were developed to quickly calculate soft, semihard and hard cheese true density on the basis of nonfat total solids or moisture and fat cheese content. Cheese density data are poor in literature and often data do not differentiate true from apparent density. Proposed equations are beneficial to researchers in food heat exchange modeling and to industry (e.g., processed cheeses, cheese cooling, freezing and thawing), because their use makes possible to estimate true density using data normally given by routine and not expensive analyses (moisture and fat cheese content), saves time and/or money compared with direct density measurement or application of the universal formula based on the determination of all the main food components.